Thermodecomposition Kinetics of Cu(II) Complex with Schiff Base Ligand - Jia, Zhen (Asian Journal of Chemistry, 2010)
A new Schiff base complex of Cu(II) has been synthesized and characterized by elemental analyses, IR and molar conductance. The thermodecom-position kinetics of the complex was investigated under non-isothermal condition TG and DTG curves indicate the complex decomposes in two steps. The kinetics of step (1) and (2) were calculated by a combination of Achar differential and Coats-Redfern integral methods.